2013
DOI: 10.1186/1475-925x-12-49
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of reconstruction of dental plaster cast from 3D digital study models

Abstract: ObjectivesTo compare traditional plaster casts, digital models and 3D printed copies of dental plaster casts based on various criteria. To determine whether 3D printed copies obtained using open source system RepRap can replace traditional plaster casts in dental practice. To compare and contrast the qualities of two possible 3D printing options – open source system RepRap and commercially available 3D printing.Design and settingsA method comparison study on 10 dental plaster casts from the Orthodontic departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
128
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(138 citation statements)
references
References 15 publications
5
128
1
4
Order By: Relevance
“…CMM analysis is widely used in dentistry to calculate the implant analog position on the x‐, y‐, and z‐axes, and is considered an accurate method to assess the dimensional discrepancies of the implant analog position between the different dental models . Previous studies, most of which focused on treatment planning and diagnosis for oral and maxillofacial surgery and orthodontics have analyzed the accuracy and precision of AM technologies . However, to the best knowledge of the authors, to date, there is no published study that analyzed the accuracy of the digital implant analog position on a 3D AM cast.…”
Section: Discussionmentioning
confidence: 99%
“…CMM analysis is widely used in dentistry to calculate the implant analog position on the x‐, y‐, and z‐axes, and is considered an accurate method to assess the dimensional discrepancies of the implant analog position between the different dental models . Previous studies, most of which focused on treatment planning and diagnosis for oral and maxillofacial surgery and orthodontics have analyzed the accuracy and precision of AM technologies . However, to the best knowledge of the authors, to date, there is no published study that analyzed the accuracy of the digital implant analog position on a 3D AM cast.…”
Section: Discussionmentioning
confidence: 99%
“…Digital modelling plays and important role in the orthodontic treatment replacing classical plaster casts by they digital models [21,22]. Digitalization of plaster casts are performed either by the 3D scanning or by processing of their stereophotos allowing to use numerical methods for evaluation of specific measures of dental arch [23,24].…”
Section: Segmentation and Three-dimensional Modelling In Orthodontiamentioning
confidence: 99%
“…Moreover, many studies have suggested that measurements derived from three-dimensional (3D) digital models have similar accuracy as those from traditional plaster casts. 7 Optical scanners can be used both in vivo and in vitro to scan the dentition or plaster casts to create digital models. 8 After making a 3D surface model of casts, the measurement of the palatal volume has been done geometrically or by creating a Computer-aided design model of the volume using reverse engineering technology.…”
Section: Introductionmentioning
confidence: 99%